Avaliação da política pública habitacional: um estudo de caso do Programa Minha Casa Minha Vida - Wittmann, Mariane Beatriz (2019)
A study proposal was carried out an evaluation of the public housing policy from the Minha Casa Minha Vida Program (PMCMV) in the Leonel de Moura Brizola Housing Estate of Santa Maria / RS involving the beneficiaries, builder and operational agent, with a guidance or improvement and inheritance of the program in the process of public planning and management, in addition to stimulating or controlling social policies. As for the method, a research characterized as an exploratory-descriptive case study, with prescribed character, possible a quantitative approach with the beneficiaries and qualitative with the construction company and operational agent. Data were collected through 144 questionnaires as beneficiary families of the program, included with an interview associated with the construction company and the operating agent, as well as field experience and related studies. For data analysis, we used the content analysis technique with qualitative approach and, with the use of descriptive statistics and factor analysis, the quantitative approach. Key findings show that beneficiaries are satisfied with home ownership and that PMCMV objectives meet beneficiaries' needs. However, when entering a specific group of activities that involve or provide habitability for the population of social interest, a relevant aspect was recorded in a housing provision that took place in a distant location from the central area, impacting some aspects of the residents' daily life. Based on the survey results, it can be concluded that the PMCMV has been improving and the evaluation of social housing programs is of important importance to professional and public policy subsidiaries with tools for policy improvement, with a view to better resource allocation and increased welfare of the population. It is highlighted here that the indicated elements, ie access to urban goods and services after the benefit, should not be included as side effects of the Program, but rather the low state capacity in the fitting room housing in specific areas.